Increasing isoniazid preventive therapy in people living with HIV in north central Nigeria: outcomes from a quality improvement strategy - Tongdiyen L Jasper, MD; Iheanyichukwu Onwubiko, MD; Imoiboho Williams, BPharm; Oriaku Ofem, MD; Uteng Wilson, MD; Hyacinth I Nnaemeka, BPharm; Iboro E Nta, MD; Young Oluokun, MD; Sunny Phillips, MD; Patrick Dakum, MD (Elsevier, 2019)
Background: Isoniazid preventive therapy (IPT) significantly reduces the incidence of active tuberculosis in people living with HIV. However, despite high tuberculosis morbidity and mortality in people living with HIV, uptake of IPT remains grossly suboptimal, with implementation impeded by several barriers related to health workers and patients. We evaluated the use of a quality improvement approach to improve IPT in a tertiary hospital in north central Nigeria with a high HIV burden. Methods: In July, 2018, a 4-week quality improvement pilot project was undertaken at the Federal Medical Centre in Keffi, Nigeria. The facility-based continuous quality-improvement committee, comprised of different cadres of staff working in the hospital's antiretroviral therapy clinic, reviewed their HIV quality-of-care indicators and noted that only 3% of eligible HIV clients received IPT between September, 2017, and March, 2018. The committee did a root cause analysis and identified poor knowledge of clinicians on the importance of IPT, fear of drug resistance, frequent stock-outs of isoniazid, and poor medication adherence as the key reasons for low rates of IPT. In response to these findings, the following key change ideas were implemented: IPT orientation for clinicians, incorporation of IPT education into routine health education for people living with HIV, display of IPT information education and communication materials in consulting and patient waiting rooms, and auditing of clients' folders prior to consultation to identify and tag eligible folders with IPT sticky notes. Findings: Between June 19, 2018, and July 17, 2018, 278 adult clients with a clinic appointment had their folders audited for IPT eligibility and 108 eligible folders (39%) were identified and tagged with an IPT sticker. Of those eligible for IPT, 103 (95%) kept their clinic appointment and all had a 6-month course of isoniazid prescribed. However, of the patients who attended, only 93 (90%) received IPT because stock of the drug had run out. Interpretation: A quality improvement strategy for improving IPT in HIV patients was effective, with 86% of eligible patients receiving treatment-an 83% increase from baseline. Quality-improvement principles such as team work and implementation of change ideas targeted at root causes of the problem were pivotal to success. Continued implementation and scale-up of effective change ideas to other hospitals could greatly reduce tuberculosis morbidity and mortality in people living with HIV, while ensuring continued availability of isoniazid. Funding: CDC-PEPFAR.